Power Mode Division Control Strategy for AC/DC Microgrids Considering SOC - Jiangzhou Cheng; Di Xiang; Cheng Fang; Zhehao Hu (Energies)
Using hybrid energy storage systems, we propose a power mode partitioning control strategy for AC/DC microgrids that effectively mitigates frequency and voltage fluctuations. By incorporating composite virtual impedance, we categorize the state of charge (SOC) into five distinct operational modes. Supercapacitors, known for their dynamic response, are prioritized to counteract power fluctuations. We assign these operational modes to the AC and DC subnetworks based on real-time changes in frequency and voltage. When significant fluctuations occur, coordinated power transmission between the subnetworks and support from the energy storage system ensure that frequency and voltage remain within acceptable limits. Simulations conducted in MATLAB/Simulink confirmed that this control strategy stabilized power fluctuations and addressed the challenges of overcharging and overdischarging in storage batteries.